Effects of soybean isoflavone aglycone on osteoporosis in ovariectomized rats - Li, Lu-lu; Yang, Yang; Ma, Chun-min; Li, Xiao-mei; Bian, Xin; Fu, Yu; Ren, Li-kun; Wang, Ru-meng; Shi, Yan-guo; Zhang, Na (Frontiers in Nutrition, 2023)
In this study, the effect of different doses of soybeans isoflavone aglycone on the ovariectomized female osteoporosis rat model was evaluated by oral gavage. There are the rats divided into seven experimental groups including SHAM, OVX, E2, SIHP, AFDP-L, AFDP-M, and AFDP-H, for which the drug was administered for 60 days from 30 days after ovariectomy. We collected blood from the abdominal aorta of rats on the 30th, 60th and 90th days respectively, analyzed its serum biochemistry, and took out the femur for micro-CT imaging and bone microstructure parameter analysis. By comparison with the OVX group, the effects on osteoporosis in the AFDP-H group were similar to those in the E2 group at 60 and 90 days, and were significantly better than those in the SIHP group. The AFDP-H group inhibited the decrease in serum bone markers, bone density, trabeculae quantity, trabeculae thickness, and bone volume fraction, and increased the trabecular separation caused by ovariectomy, thereby significantly improving bone microstructure. It also prevented continuous weight gain and increased cholesterol levels in female rats. In conclusion, this study showed that soybeans isoflavone aglycone could effectively inhibit and improve osteoporosis symptoms in ovariectomized rats.